Peroxiredoxin 6 Knockout Mice Demonstrate Anxiety Behavior and Attenuated Contextual Fear Memory after Receiving Acute Immobilization Stress - Sarayut Phasuk; Peeraporn Varinthra; Andaman Nitjapol; Korakod Bandasak; Ingrid Y. Liu (MDPI AG, 2021)
Stress can elicit glucocorticoid release to promote coping mechanisms and influence learning and memory performance. Individual memory performance varies in response to stress, and the underlying mechanism is not clear yet. Peroxiredoxin 6 (PRDX6) is a multifunctional enzyme participating in both physiological and pathological conditions. Several studies have demonstrated the correlation between PRDX6 expression level and stress-related disorders. Our recent finding indicates that lack of the Prdx6 gene leads to enhanced fear memory. However, it is unknown whether PRDX6 is involved in changes in anxiety response and memory performance upon stress. The present study reveals that hippocampal PRDX6 level is downregulated 30 min after acute immobilization stress (AIS) and trace fear conditioning (TFC). In human retinal pigment epithelium (ARPE-19) cells, the PRDX6 expression level decreases after being treated with stress hormone corticosterone. Lack of PRDX6 caused elevated basal H2O2 levels in the hippocampus, basolateral amygdala, and medial prefrontal cortex, brain regions involved in anxiety response and fear memory formation. Additionally, this H2O2 level was still high in the medial prefrontal cortex of the knockout mice under AIS. Anxiety behavior of Prdx6−/− mice was enhanced after immobilization for 30 min. After exposure to AIS before a contextual test, Prdx6−/− mice displayed a contextual fear memory deficit. Our results showed that the memory performance of Prdx6−/− mice was impaired when responding to AIS, accompanied by dysregulated H2O2 levels. The present study helps better understand the function of PRDX6 in memory performance after acute stress.